From Passion to Intention: Investing, Funding, and Developing Passion in Student Entrepreneurship - Daniel Joel Immanuel Kairupan (Telaah Bisnis, 2026)
Entrepreneurial passion has been theorized as a critical affective antecedent of entrepreneurial intention; however, the distinct and comparative contributions of its three domain-specific dimensions, passion for investing, passion for funding, and passion for developing remain insufficiently examined within a unified empirical model. Grounded in the Theory of Planned Behavior and the entrepreneurial passion framework, this study investigates the influence of these three passion dimensions on entrepreneurial intention. A quantitative cross-sectional design was employed, with data collected from 190 respondents using a structured questionnaire. Hypothesized relationships were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The results confirm that all three dimensions exert significant positive influences on entrepreneurial intention, with passion for developing emerging as the strongest predictor (β = 0.363, t = 9.571, p < 0.001), followed by passion for investing (β = 0.328, t = 5.257, p < 0.001) and passion for funding (β = 0.223, t = 3.571, p < 0.001). These findings demonstrate that entrepreneurial intention is substantially driven by domain-specific affective orientations embedded within the individual's entrepreneurial identity, extending beyond purely cognitive determinants. This study contributes theoretically by integrating passion-based antecedents into a unified predictive model of entrepreneurial intention and offers practical implications for the design of entrepreneurship education programs that deliberately cultivate affective engagement alongside technical skill development. Policymakers and educators are encouraged to incorporate passion-nurturing pedagogical approaches, particularly those emphasizing developmental and investment orientations, to foster stronger and more sustained entrepreneurial intentions among prospective entrepreneurs.